Leaf Blight of Some Hardwood Species in Assam and Meghalaya and its Control in the Nursery - Mehrotra, M. D. (Indian Forester, 1989)
The paper gives an account of leaf web-blight of Melia azedarach Linn., Azadirachta indica A. Juss., Cassia nodosa Ham, Ceiba pentandra (Linn.) Gaertn. And Derris robusta Benth. Caused by Rhizoctonia solani anamorph of Thanatephorus cucumeris (Frank) Donk and leaf blight of Engelhardtia spicata Blume caused by Sclerotinia sclerotiorum (LIB.) de Bary. These diseases are recorded for the first time in India. The Rhizoctonia web blight was highly destructive in the nursery. It damaged the foliage as well as killed the heavily infected young seedlings. M. azedarach and A. indica were highly susceptible to the disease and the damage to the foliage was to the extent of 80-90%. Obviously, this had perceptible impact on the growth of the seedlings in these two species. The existence of more than one strain of the pathogen in the forests at Burnihat is emphasized. The disease may be kept under check by avoiding dense sowing of seed and removal of the infected seedlings as soon as the disease appears in the bed. In case of M. azedarach and A. indica which are highly susceptible to the disease, it is recommended that these two species be raised in pathogen, presumably soil borne, is easily carried to the plant parts close to the ground through splashing and thus it is likely to cause heavy damage to the susceptible species raised in beds. However, the chances of infection through splashing are very much reduced if the seedlings are raised in polypots. Moreover, it has been found that A. indica when raised in polypots at Burnihat was almost free from the disease.